An innovative MS-VAR model with integrated financial knowledge for measuring the impact of stock market bubbles on financial security - Chao Zheng (Journal of Innovation & Knowledge, 2022)
In the modern financial system, division of labor and close cooperation between different departments are determinants of risk contagion. The risk resulting from the volatility of the stock market can easily spread to other industries and departments, leading to systemic financial and economic crises. Previous research has mostly examined financial security from the lens of macro currency security, and the security of the banking system, but has ignored its micro-basic problems, such as the bounded rationality of investors due to the lack of financial knowledge. The study analyzes the behavior of micro-investors, price fluctuations in the meso‑stock market, and the macro-financial security in a unified framework. First, we use the comprehensive analysis method to superimpose some basic values and investor behavior characteristics, such as the stock price fluctuation index, and then construct the ultimate stock price bubble index; second, the principal component method is used to establish a financial security index that is in line with basic economic reality and consistent with previous studies; the innovative MS-VAR model is used to analyze whether the stock price bubble will affect financial security, and the rhythm and correlation of the two parties under different regimes are summarized. The results show that the stock market bubble level is the Granger cause of financial security, the stock market bubble index is the leading indicator of the financial security index, and the relevant parameters of the model are significant and have obvious economic significance. This study has important implications for scientific market regulation.